The Effect of Service Quality of Pamanukan Medical Centre Hospital on Outpatient Satisfaction in Subang Regency - yani, Sri; Hidayatulloh, Faizal; Oktriani, Anggun (ADMAN: Journal of Contemporary Administration and Management, 2023)
In the Non-Probability Sampling method which uses purposive sampling, this study discusses the quality of service on patient satisfaction. The research objective is to find out whether or not there is an influence on service quality on patient satisfaction. The sample taken used 5 respondents and 5 questionnaires. And the hypothesis used is service quality (X) and patient satisfaction (Y). Based on the results obtained in this research that for service quality that has a positive effect on patient satisfaction.